Dimensi -dimensi agama menurut teori Allport GW dan Ross JM - Wardania, Siti (Maliki Interdisciplinary Journal, 2024)
This study discusses the dimensions of religion according to Gordon Allport’s theory, particularly focusing on intrinsic and extrinsic religiosity. Intrinsic religiosity reflects deep-seated beliefs in religion, while extrinsic religiosity is more focused on external benefits or personal interests. Individuals with intrinsic religiosity tend to act in accordance with religious principles and allocate time for prayer. On the other hand, individuals with extrinsic religiosity may engage in religious activities to gain social support or enhance social status. This understanding provides insights into the role of religion in shaping individual behavior and values, as well as the importance of understanding the differences between intrinsic and extrinsic motivations in the context of religion.